ChemInform Abstract: Catalytic Asymmetric Construction of Pyrroloindolines via an in situ Generated Magnesium Catalyst. Issue 23 (June 2015) - Wang, Linqing; Yang, Dongxu; Han, Fengxia; Li, Dan; Zhao, Depeng; Wang, Rui
Abstract Starting from 2, 3‐substituted aziridines and 3, 4, 5‐ and 6‐substituted indoles the polycyclic products are obtained with moderate to high yields and high enantiomeric excess.